Proceedings of the 2011 Winter Simulation Conference (WSC) 2011
DOI: 10.1109/wsc.2011.6148100
|View full text |Cite
|
Sign up to set email alerts
|

A regularized adaptive steplength stochastic approximation scheme for monotone stochastic variational inequalities

Abstract: Motivated by problems arising in decentralized control problems and non-cooperative Nash games, we consider a class of strongly monotone Cartesian variational inequality (VI) problems, where the mappings either contain expectations or their evaluations are corrupted by error. Such complications are captured under the umbrella of Cartesian stochastic variational inequality problems and we consider solving such problems via stochastic approximation (SA) schemes. Specifically, we propose a scheme wherein the step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…A key shortcoming of standard stochastic approximation schemes is the relatively ad hoc nature of the choice of step-length sequences. Yousefian et al [116,117] developed distributed stochastic approximation schemes where users can independently choose a step-length rule. Importantly, these rules collectively allow for minimizing a suitably defined error bound and are equipped with almost-sure convergence guarantees.…”
Section: Variational Inequality Problems Under Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…A key shortcoming of standard stochastic approximation schemes is the relatively ad hoc nature of the choice of step-length sequences. Yousefian et al [116,117] developed distributed stochastic approximation schemes where users can independently choose a step-length rule. Importantly, these rules collectively allow for minimizing a suitably defined error bound and are equipped with almost-sure convergence guarantees.…”
Section: Variational Inequality Problems Under Uncertaintymentioning
confidence: 99%
“…Although, this choice allows for almost-sure convergence, it has been observed that such choices may lead to poor performance in practice. Motivated by this shortcoming, Yousefian et al [117,116] developed step-length rules that allow for prescribing step-length sequences in accordance with problem parameters. More specifically, such a rule derived a sequence in a convex stochastic optimization regime by leveraging three parameters: (i) Lipschitz constant of the gradients, (ii) strong convexity constant, and (ii) diameter of the set X.…”
Section: Self-tuned Stochastic Approximation Schemesmentioning
confidence: 99%
“…It can be shown that the mapping F is strongly monotone and Lipschitz with specified parameters (cf. [19]). We solve the bandwidth-sharing problem for 12 different settings of parameters shown in Table I.…”
Section: A a Bandwidth-sharing Problem In Computer Networkmentioning
confidence: 99%
“…Lizarraga et al [14] considered a family of two person Mutil-Plant game and developed Stackelberg-Nash equilibrium conditions based on the Robust Maximum Principle. More recently, Yousefian et al [1], [15] developed centralized adaptive stepsize SA schemes for solving stochastic optimization problems and variational inequalities. The main contribution of the current paper lies in developing a class of distributed adaptive stepsize rules for SA scheme in which each agent chooses its own stepsizes without any specific information about other agents stepsize policy.…”
Section: Introductionmentioning
confidence: 99%
“…The second approach, inspired by the seminal work by Robbins and Monro [10], is that of stochastic approximation and there has been a surge of recent effort applying such techniques to stochastic variational inequality problems [11], [12], [13], [14]. While most of the above contributions rely on standard diminishing steplength sequences, Yousefian and his coauthors [15], [16] propose techniques in which the steplength sequences are tuned to problem parameters and minimize a suitably defined meansquared error bound. Yet, almost of these statements are limited by their ability to accommodate strongly, strictly, or merely monotone maps.…”
Section: Introductionmentioning
confidence: 99%